Traumatic coagulopathy and massive transfusion: improving outcomes and saving blood - Karim Brohi; Simon Eaglestone (NIHR Journals Library, 2017)
Introduction: Dysfunction of the coagulation system, termed trauma-induced coagulopathy (TIC), is a major problem in patients who bleed after injury. Trauma haemorrhage is considered one of the leading preventable causes of death worldwide. Deaths occur early and, despite the presence of trauma teams and large transfusions of blood products, outcomes remain poor. Methods: We conducted a multimodal programme of work to develop our understanding of coagulopathy and its optimal management. We studied the epidemiology, management and health economics of trauma haemorrhage, including the provision of care during mass casualty events. We combined systematic reviews of the literature with a national study of trauma haemorrhage, its transfusion management and associated health-care costs. We further examined several point-of-care coagulation tools for their ability to diagnose coagulopathy and assess the response to blood component therapy. We progressively implemented our findings into practice and assessed the outcomes of trauma patients presenting to our major trauma centre. To examine different approaches to the provision of blood to casualties in a mass casualty event, we constructed a discrete event model based on data from the 2005 London bombings. Key results: Our systematic reviews found little strong evidence for the existing diagnostic tools or the practice of delivery of blood components in trauma haemorrhage. Our national study recruited 442 patients in 22 hospitals and found that the 1-year mortality rate for massive haemorrhage approached 50%. Half of these deaths occurred in the first 24 hours after injury and half of these occurred in the first 4 hours. We identified this early time window as a period when the provision of blood component therapy was often below the recommended thresholds and blood component therapy was delivered inconsistently. Studying early TIC we determined that loss of fibrinogen and excessive fibrinolysis were key derangements. We were able to determine that rotational thromboelastometry could identify early coagulopathy within 5 minutes, a large improvement on laboratory tests. We were further able to show how existing damage control resuscitation regimens with high-dose plasma do not maintain haemostatic competency during haemorrhage. In total, the estimated cost of treating a major haemorrhage patient was £20,600 and the estimated cost of treating a massive haemorrhage patient was £24,000. Nationally, the estimated cost of trauma haemorrhage is £85M annually. In mass casualty situations, early results show that the only mutable factor that affects the provision of care to a large degree, in the initial phase of the response, is the level of blood stocks held in the receiving hospital. Conclusions: This multimodal programme of work has led to new understandings of the epidemiology of trauma haemorrhage and its underlying mechanisms and clinical course. We have defined diagnostic tools and trigger thresholds for identification and management and increased our understanding of how blood component and other therapeutics affect coagulopathy and when they are likely to be most effective. This diagnostic work has been taken forward at an international level to produce new personalised guidelines for the management of trauma haemorrhage. The findings have had important therapeutic implications, which have led to important changes in practice that have been incorporated into new national and international guidelines. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.